Sheep production in the humid zone of West Africa. II. Growth performance and liveweight of sheep in improved and traditional production systems in Cote d'Ivoire - Armbruster, T.; Peters, Kurt J.; Metz, T. (Wiley, 1991)
Presents the growth performance data of mainly indigenous trypanotolerant Djallonke sheep kept under traditional or improved management conditions in the humid south-east of Cote d'Ivoire; and reports that most lamb weights were significantly influenced by birth season.